Study on the relationship between depressive symptoms and Internet use in the older adults under the background of population aging—evidence based on CHARLS 2018 and 2020 - Mengzi Guo; Zihang Li; Yixuan Chen; Xiangwan Chen; Zhi Cheng; Zhiru Tang (BMC Public Health)
Abstract Background Research has identified the effect of Internet use on depressive symptoms, where as the results remain controversial. Given the fact that both Internet use and depressive symptoms are in dynamic change, this paper focuses on the relationship between depressive symptoms and Internet use among Chinese elderly people in the context of population aging, which could generate targeted policy recommendations aimed at safeguarding the healthy development of older adults and provide an important basis for the government to build a more inclusive aging society. Methods A total of 15,637 samples were extracted for analyses using CHARLS (China Health and Retirement Longitudinal Study) data after matching the 2018 and 2020 data by sample-identified correlation IDs (including ID, household ID, and community ID). The matching was intended to reduce the potential for confounding variables that could arise if the two datasets included different individuals, and make it easier to draw conclusions about the relationship between depressive symptoms and Internet use over time for the consistent people. Statistical analyses were performed using SPSS 28.0 and STATA software. Measurement data were expressed as $$\overline{x }± s$$ x ¯ ± s and count data were expressed as frequency (%). Comparisons between groups were performed using t-test and ANOVA (The Analysis of Variance). Correlation analyses were performed using multiple linear regression and ordered probit regression analyses, and the test level was set at α = 0.05. Results Older adults with greater device ownership had less severer depressive symptoms (P < 0.001) and those without Internet access (P < 0.05) had severer depressive symptoms. Older adults who didn't use mobile phones to pay (P < 0.001) and didn't use WeChat (P < 0.05) or post to their friends (P < 0.001) had severer depressive symptoms. The impact of Internet use was more evident among older adults who self-assessed health very good, were relatively younger, urban, and in marriage (P < 0.05). Conclusions Internet use might have a significant impact on depressive symptoms among older adults in the context of population aging.